PENINGKATAN DISIPLIN GURU DALAM MENGUMPULKAN PERANGKAT PEMBELAJARAN MELALUI SISTEM REWARD DAN PUNISHMENT SMA INS KAYU TANAM - Hendrizal Hendrizal (STKIP Pesisir Selatan, 2018)
Abstract Based on the results of observations that researchers do in the semester of January-August 2017/2016, researchers found the phenomenon that the level of discipline of teachers in collecting learning tools is still low. This is evident from the time the researcher asked the teacher to collect learning tools there are still many teachers who did not collect the requested learning device. There are also teachers who rush to prepare learning tools when the principal or supervisor will supervise the class. Of the six class teachers, if averaged, then only 60%, teachers who complement the learning tools both in the form of syllabus, SK / KD, RPP, prota promes and teaching materials. Meanwhile, 40% of teachers did not collect. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The research subjects consisted of 6 teachers of INS Kayu Tanam high school class who were research class teachers. Research data was collected using obeservation sheets. Data were analyzed using percentages. Based on the result of research, it can be concluded that the application of reward and punishment system can improve teacher discipline in collecting learning device. This is evidenced from before applied rewards and punishment, the percentage of teachers who collect learning tools only 66.67% with the collect on time only amounted to 22.81%. After applied reward and punishment system, then in cycle I, teacher collecting learning device become 79,65% with percentage which collect on time is 35,79%. After cycle II, the percentage of teachers who collected learning tools became 97.54% with the percentage of teachers who collected on time was 81.05%. Keywords: Discipline, Learning Device, Reward and Punishment